1982
DOI: 10.1007/bf00542547
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of pindolol in patients with renal failure

Abstract: Increased metabolism of pindolol in renal impairment has previously been suggested by pharmacokinetic calculations. The present study was a pharmacokinetic and metabolic investigation in 7 patients with severe renal impairment (endogeneous creatinine clearance below 5 ml/min). All the patients received pindolol 5 mg t.d.s. 5 days. On the sixth day, after an overnight fast, 14C-pindolol 5 mg was given orally as a solution to drink. Blood samples were taken for up to 72 h and urine was collected at intervals up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1984
1984
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…However, these values can change according to the therapeutic protocol and in pathological conditions: for example, the AUC for atenolol in patients with terminal renal failure increases to 500 μM·h . Down-regulation of OCT in renal failure, as experimentally demonstrated here and elsewhere, ,, may be the reason for increased steady state plasma concentrations and/or elimination half-life observed for atenolol, pindolol, and ofloxacin in patients with renal disease.…”
Section: Discussionmentioning
confidence: 71%
“…However, these values can change according to the therapeutic protocol and in pathological conditions: for example, the AUC for atenolol in patients with terminal renal failure increases to 500 μM·h . Down-regulation of OCT in renal failure, as experimentally demonstrated here and elsewhere, ,, may be the reason for increased steady state plasma concentrations and/or elimination half-life observed for atenolol, pindolol, and ofloxacin in patients with renal disease.…”
Section: Discussionmentioning
confidence: 71%
“…If metabolism in the kidney were an important route of elimination, one might expect that the metabolic clearance of pindolol would be impaired in the diseased kidneys. In patients with liver disease, a substantial decrease in the clearance of racemic pindolol has been observed, which suggests that the metabolism of pindolol is occurring to a large extent in the liver (15,16 Another mechanism that may have been responsible for the stereoselective renal clearance of pindolol is stereoselective renal transport. In agreement with other studies (12,17), we observed that the renal clearance of unbound pindolol was greater than the GFR, which indicates that pindolol is actively secreted by the kidneys.…”
Section: Discussionmentioning
confidence: 99%
“…13 Pindolol metabolites excreted in urine are mainly glucuronides, hydroxy-glucuronides, or hydroxysulphates, products which are dependent on the activity of UDP-glucuronosyltransferases, cytochrome P-450 system, or arylsulfatases. 9,19 Hormonal factors play an important role in the regulation of glucuronidation activity. 20 The increased clearance of oxazepam and paracetamol in pregnant women, as well as of paracetamol, temazepam, and clofibric acid in patients treated with oral steroid contraceptives, demonstrates the influence of sex-related factors on the glucuronidation-dependent elimination of drugs.…”
Section: Resultsmentioning
confidence: 99%
“…7 Pindolol is cleared approximately equally by both metabolism and renal excretion. 6,[8][9][10] The renal clearance of racemic pindolol exceeds the glomerular filtration rate, indicating that the drug is actively secreted. 8,11 Hsyu and Giacomini 8 reported that the renal elimination of pindolol is stereoselective in healthy subjects.…”
mentioning
confidence: 99%